Dreams Deterred: The Collateral Consequences of Localized Immigration Policies on Undocumented Latinos in Colorado. (29th January 2019) - Martinez, Lisa M.; Ortega, Debora M.
Abstract : Recent years have seen a broadening of the scope of immigration enforcement. As a result, immigrants free of criminal convictions, once considered low priorities for enforcement, are increasingly subject to arrest, detention, and removal. At the same time, federal immigration authorities have sought the cooperation of states and localities in the enforcement of immigration laws. While there has been growing scholarly attention paid to the ways in which legal geographies can account for variation in local immigration policies, the long‐term effects of these policies on immigrants themselves are often overlooked. In this article, we use the case of Colorado, one of the first states to pass a "show‐me‐your‐papers" law in 2006, and data from two qualitative studies to highlight the collateral consequences of enhanced immigration enforcement on immigrants' economic opportunities, emotional health and well‐being, and academic trajectories. We situate our analysis within the crimmigration literature and discuss the implications of our findings in light of the current political climate.